Pengaruh Pelayanan Customer Service terhadap Kepuasan Nasabah Bank Syariah - Arni Fadilah; Irwan Habibi Hasibuan (STEBI Global Mulia Cikarang, 2022)
The influence of service plays an important role in a company, because the company's success in expanding the market is by producing goods or services according to predetermined quality standards, as well as providing excellent service in the service sector. And Customer Satisfaction is the level of one's feelings after comparing the performance that is felt in accordance with his expectations. The purpose of this study was to determine the effect of customer service on Islamic banking customer satisfaction in students of the STEBI Global Mulia Cikarang Islamic Banking Study Program. The method in this research is quantitative research. The population used in this study were STEBI Global Mulia students from the Islamic Banking study program batch 2018-2021, totaling 120 students. Data collection techniques using questionnaires, observation and documentation. The processed data is validity test, reliability test, classical assumption test and simple regression. The results of this study indicate that Islamic bank customer service with a known tcount value of the Customer service variable (X) is 9.404 and a ttable value of 1.990 means 9.404 > 1.990 thus Ha is accepted and Ho is rejected. As well as a significant value of 0.000 more than 0.05, it can be concluded that Islamic bank customer service (X) empirically has a positive effect on customer satisfaction at STEBI Global Mulia students.